(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The way a child learns and learns about the world is determined by his or her age. The educator activates the cognitive abilities of preschool children through cognitive tasks and allows them to systematize children’s knowledge. The process of performing cognitive tasks is accomplished through voluntary, intellectual action, which results in positive activities that complete the cognitive movement.